Relokasi Permukiman Desa Suka Meriah Akibat Kejadian Erupsi Gunung Api Sinabung Kabupaten Karo (Settlement Relocation of Suka Meriah Village as an Impact of Mount Sinabung Eruption in Karo Regency) - Stenfri Loy Pandia; Rini Rachmawati; Estuning Tyas Wulan Mei (The Institute for Research and Community Services, Institut Teknologi Bandung, 2016)
Suka Meriah Village is one of the villages that experienced heavy damage because it is located 3 km from the peak of Mount Sinabung and is also located within Disaster Prone Area (KRB) III. One of the best solutions to minimize the negative impact of the disaster is to relocate the Suka Meriah Village to a safer location capable of accommodating the entire population including its needs for facilities and infrastructure. The purpose of the research is to identify community perception on the settlement relocation plan, to analyze the local condition of the relocation area and to assess problems in the settlement relocation plan. The research uses qualitative research methods, where primary data is obtained through observation and semi-structured interviews and secondary data is obtained from literature and agencies data. The research shows that in general, the Suka Meriah Village community agrees with the relocation plan. The relocation settlement is located in the Siosar Area. In general, until the end of the research period in August 2015, the construction of the new settlement in the Siosar Area has not been completed because it was still in the construction process. The problem that occurred was that the relocation process was slow. As a result, the economic activities of the community were restricted.Besides this, the government aid was insufficient to fulfill their daily needs.